2021
DOI: 10.3389/fimmu.2021.629519
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Melanoma: Mutational Status and Potential Links to Tertiary Lymphoid Structure Formation

Abstract: Recent advances in immunotherapy have enabled rapid evolution of novel interventional approaches designed to reinvigorate and expand patient immune responses against cancer. An emerging approach in cancer immunology involves the conditional induction of tertiary lymphoid structures (TLS), which are non-encapsulated ectopic lymphoid structures forming at sites of chronic, pathologic inflammation. Cutaneous melanoma (CM), a highly-immunogenic form of solid cancer, continues to rise in both incidence and mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 120 publications
0
11
0
Order By: Relevance
“…These features are also related to the reduced DNA repair ability and high mutational load of melanoma cells, which make it easier to transform the TME into a “hot tumor” and form an environment that induces TLS formation. 61 In addition, the existence of TLSs is closely related to immune checkpoint blockade (ICB). 38 Remark et al 62 found that TLSs were present in the tumors of patients undergoing neoadjuvant therapy (PD-1 inhibitor), which was associated with longer disease-free survival and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…These features are also related to the reduced DNA repair ability and high mutational load of melanoma cells, which make it easier to transform the TME into a “hot tumor” and form an environment that induces TLS formation. 61 In addition, the existence of TLSs is closely related to immune checkpoint blockade (ICB). 38 Remark et al 62 found that TLSs were present in the tumors of patients undergoing neoadjuvant therapy (PD-1 inhibitor), which was associated with longer disease-free survival and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…TLS are established at sites of chronic inflammation and can structurally and functionally resemble secondary lymphoid organs (120)(121)(122). Recent studies on murine models of TLS have shown the role of PDPN+ FAP+ immunofibroblasts in driving the development and expansion of TLSs (123,124).…”
Section: Tertiary Lymphoid Structures (Tls)mentioning
confidence: 99%
“…This operating paradigm may underlie observations of cancers with reduced DNA repair proficiency and high comparative mutational burden presenting with brisk proinflammatory immune cell infiltrates (i.e. “hot tumors”) that are more prone to develop TLS ( 69 , 70 ) and to be more responsive to interventional immunotherapy ( 71 , 72 ). Notably, provision of low doses of STING agonists cGAMP and ADU-S100 (aka ML-RR-S2-CDA, MIW815) coordinately promote VN and CD8 + T cell-dependent control of tumor growth in murine models of breast carcinoma, lung carcinoma and melanoma ( 67 , 68 , 73 ).…”
Section: Sting Signaling Enforces a Pro-inflammatory Pro-tls Tmementioning
confidence: 99%